Effect of Pyridoxine on Prostaglandin Plasma Level for Primary Dysmenorrheal Treatment: Pengaruh Pemberian Piridoksin terhadap Kadar Prostaglandin Plasma sebagai Terapi Dismenore Primer - Ervan J Randabunga; Efendi Lukas; Josephine L Tumedia; St. Maisuri T. Chalid (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective : To determine the effect of vitamin B6 (pyridoxine) the levels of prostaglandins and intensity of pain in primary dysmenorrheal. Methods : The levels of prostaglandin (PGF2Î±) in plasma measured by ELISA and pain intensity by verbal rating scales conducted on 35 women with primary dysmenorrheal (n=35) supplemented with vitamin B6 100mg for 4 days and controls with placebo (n=35). Results : Prostaglandin levels decreased significantly after vitamin B6 supplementation (2212.9+1374.2 vs 1490.3+1119.0; p<0.05) followed by a significant reduction in pain intensity (4.29+0.7 vs 1.71+0.5; p<0.05) in the test group compared to control. Conclusion : Due to vitamin B6 effects on decreasing prostaglandin levels and pain of primary dysmenorrheal, so that B6 vitamin can become the treatment for the primary dysmenorrheal. Keywords : Primary dysmenorrheal, pyridoxine, prostaglandin Tujuan: Untuk mengetahui pengaruh pemberian vitamin B6 (piridoksin) terhadap kadar prostaglandin dan intensitas nyeri pada dismenore primer. Metode: Pemeriksaan kadar prostaglandin (PGF2Î±) dengan ELISA dan pengukuran intensitas nyeri dengan verbal rating scales dilakukan pada 35 orang (n=35) wanita dengan dismenore primer yang mendapatkan vitamin B6 100mg selama 4 hari dan kontrol yang mendapatkan plasebo (n=35). Hasil: Kadar prostaglandin menurun bermakna setelah pemberian vitamin B6 (2212,9+1374,2 vs 1490,3+1119,0; p<0,05) disertai dengan penurunan intensitas nyeri yang bermakna (4,29+0,7 vs 1,71+0,5; p<0,05) pada kelompok uji dibandingkan kontrol. Kesimpulan: Vitamin B6 menurunkan kadar prostaglandin dan nyeri sehingga vitamin B6 dapat dipertimbangkan menjadi salah satu pengobatan dismenore primer. Kata kunci : Dismenore primer, piridoksin, prostaglandin